2018
DOI: 10.1108/hff-07-2018-0374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field-dependent thermal conductivity on natural convection of magnetic nanofluid inside a square enclosure

Abstract: Purpose The purpose of this paper is to investigate the convective heat transfer of magnetic nanofluid (MNF) inside a square enclosure under uniform magnetic fields considering nonlinearity of magnetic field-dependent thermal conductivity. Design/methodology/approach The properties of the MNF (Fe3O4+kerosene) were described by polynomial functions of magnetic field-dependent thermal conductivity. The effect of the transverse magnetic field (0 < H < 105), Hartmann Number (0 < Ha < 60), Rayleigh nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Results obtained showed that Nusselt number increased with the increase of volume concentration and magnetic field strength. More numerical work by Hajiyan et al 10 and found that heat transfer is enhanced with the presence of magnetic field when magnetic nanofluids was inside a square enclosure. Vafeas et al 11 studied the effects of applying different magnetic field and volume concentration, respectively on a laminar flow in a different curved cylindrical annular duct.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained showed that Nusselt number increased with the increase of volume concentration and magnetic field strength. More numerical work by Hajiyan et al 10 and found that heat transfer is enhanced with the presence of magnetic field when magnetic nanofluids was inside a square enclosure. Vafeas et al 11 studied the effects of applying different magnetic field and volume concentration, respectively on a laminar flow in a different curved cylindrical annular duct.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth declaring that oxidation of MNPs are considered biocompatible because the particle cell homeostasis is efficiently controlled by uptake, excretion and storage (Jain et al , 2008). Furthermore, MNPs can undoubtedly be among the potential techniques in biomedical applications such as magnetic scaffolding, cell therapy, MRI, gene delivery, hyperthermia, drug delivery and cell labeling (Thiesen and Jordan, 2008; Ito et al , 2001; Plank et al , 2003; Roger et al , 1999; Dinarvand et al , 2019; Hajiyan et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection occurs when the fluid motion is induced by the density variations based on the temperature difference within the fluid (also termed as buoyancy-driven convection). Applications of natural convection involve material processing (Mohamad et al , 2019), phase change materials (Ben Salah and Ben Hamida, 2019), cooling of electronic equipment (Bairi et al , 2019), heat exchangers (KhakRah et al , 2019) and nanofluids (Mahmoudi et al , 2013; Cho et al , 2013; Selimefendigil et al , 2016; Bondareva et al , 2017; Mansour et al , 2017; Shirvan et al , 2017; Sabour et al , 2017; Sheremet et al , 2017; Alsabery et al , 2018; Armaghani et al , 2019a, 2019b; Biswal et al , 2019; Cimpean and Pop, 2019; Dogonchi et al , 2019; Dutta et al , 2019; Ghalambaz et al , 2019; Gireesha and Sindhu, 2019; Hajiyan et al , 2019; Ishak et al , 2019; Izadi et al , 2019; Khan et al , 2019a; Mohebbi et al , 2019; Rashidi et al , 2019; Shashikumar et al , 2019; Shahsavar et al , 2019; Sreedevi et al , 2019; Tayebi and Chamkha, 2019). Das et al (2017) highlight the importance of natural convection associated with the thermal performance of various process applications.…”
Section: Introductionmentioning
confidence: 99%
“…Average Nusselt number ( Nubtrue¯) and average dimensionless spatial temperature ( trueθ^) are also evaluated via the finite element basis sets. Finite element-based simulations had also been used extensively by various researchers for computational fluid dynamics (CFD)-based studies (Sreedevi et al , 2019; Rafiei et al , 2019; Hajiyan et al , 2019). Current simulations are carried out for Ra = 10 3 −10 5 at Pr = 155.…”
Section: Introductionmentioning
confidence: 99%